Opening Area usage of Shear Wall Relating to Wall Area Used for Multistoried Building: A Review - Singh, Krishna Pal (International Journal of Advanced Engineering Research and Science, 2021)
In this present era of high-rise buildings and skyscrapers it is obligatory to work on overall shape, plan and structure of building. The building performance under seismic loading is a constraint of various factors comprises of geometry, location and the way of earthquake forces transferred to the ground. The affected zones of higher chances of occurrence of seismic effects with respect to other part of the country may leads to collapse of building under seismic load if they are not provided with and structural strengthening arrangement. However, safety has to be the main criteria when seismic hazard has taken into account in multistoried buildings. In the current study the solution for aforementioned problem is suggested by providing shear wall in a specified ratio with respect to wall area in plan irregularity which helps in resisting lateral load generated by seismic forces. This paper provides the review of research work previously presented by various researchers which shows the further research option.